Creative regions : technology, culture and knowledge entrepreneur ship - Schwartz, Dafnah (London ; New York : Routledge, Taylor & Francis Group, 2007)
The contributors to this text focus on regional creativity, analysin g the different factors that can affect creativity and innovation proce ss within regions in the knowledge economy.
Creative regions : an introduction / Philip Cooke, Dafna Schwartz -- Regional innovation systems -- The regionalisation of knowledge : the territorial basis of development / Dietmar Bastian, Ulrich Hilpert -- C reative regions and globalising social capital : connecting foreign ICT experts to Finnish innovation environments / Mika Raunio -- Connectivi ty and co-location in innovation processes of Dutch firms / Pieter J.M. de Bruijn, Frank. G. van Oort -- On strengthening the knowledge base o f knowledge-intensive SMEs in less-favoured regions in Finland / Kati-J asmin Kosonen -- Cluster evolution, variety and policy -- Regional inno vation clusters : evaluation of the South East Brabant cluster scheme / Roel Rutten, Frans Boekema -- Cluster emergence : a comparative study of two cases in North Jutland, Denmark / Dagmara Stoerring, Bent Dalum -- The knowledge-space dynamic in the British biotechnology industry : function, relation, and association / Kean Birch -- Culture, creativity and local development : evidence from creative industries in Florence / Luciana Lazzeretti -- Reflections on innovative alliances involving t echnological science and the creative industry : a case study involving the Roskilde Region and Musicon Valley / Birgitte Rasmussen, Jens-Pete r Lynov -- Knowledge transfer, R & D outsourcing, open innovation -- Re search, knowledge and open innovation : spatial impacts upon organisati on of knowledge-intensive industry clusters / Philip Cooke -- The outso urcing of knowledge production and its implications for regional path d ependence / Alex Burfitt, Chris Collinge -- Creativity and openness : o utsourcing of knowledge-intensive services as a challenge for innovatio n systems in a metropolitan region / Rèudiger Wink -- Boundary spanning and the "knowledge community" / Hiro Izushi.
"Simultaneously published in the USA and Canada."--Title page verso.
Includes bibliographical references and index.
Keywords: Regional economics; High technology industries -- Location; High technology industries -- Location -- Case studies; Technological innovations -- Government policy; Knowledge management; Entrepreneurship